Knowledge of early detection of peripartum cardiomyopathy and postpartum help-seeking practices - Suryani Manurung; Dinny Atin Amanah; Emy Rianti; Ulty Desmarnita (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2026)
Background: Peripartum Cardiomyopathy (PPCM) is a life-threatening form of heart failure that can occur during the late stages of pregnancy or in the postpartum period. Limited knowledge among postpartum mothers regarding early detection of PPCM may contribute to delays in seeking appropriate medical care, thereby increasing the risk of severe complications. Purpose: To determine mothers' knowledge of early detection of peripartum cardiomyopathy and postpartum help-seeking practices. Method: A quantitative analytical design with a cross-sectional approach. The population consisted of postpartum mothers within 0–6 months after delivery. A total of 236 respondents were selected using purposive sampling. Data were collected using structured questionnaires measuring knowledge of early detection of PPCM and medical care-seeking behavior. Data analysis included univariate analysis and bivariate analysis using the chi-square test. Results: The majority of respondents were within the healthy reproductive age range, with a mean age of 28.44 years, and most did not experience symptoms related to PPCM during pregnancy or after childbirth. Most respondents demonstrated a good level of knowledge regarding early detection of PPCM. The chi-square test showed no statistically significant association between postpartum mothers’ knowledge of early detection of PPCM and their medical care-seeking behavior (p = 0.704). Conclusion: Knowledge of early detection of Peripartum Cardiomyopathy among postpartum mothers has not yet been reflected in their medical care-seeking behavior. Other factors, including risk perception, family support, accessibility of health services, and cultural influences, may play a more substantial role. Strengthening continuous health education, family-centered interventions, and community-based early detection programs is recommended to prevent PPCM-related complications.